2023
DOI: 10.1021/acs.est.3c03458
|View full text |Cite
|
Sign up to set email alerts
|

Widespread Distribution of the arsO Gene Confers Bacterial Resistance to Environmental Antimony

Shi-Tong Tang,
Xin-Wei Song,
Jian Chen
et al.

Abstract: Microbial oxidation of environmental antimonite (Sb(III)) to antimonate (Sb(V)) is an antimony (Sb) detoxification mechanism. Ensifer adhaerens ST2, a bacterial isolate from a Sb-contaminated paddy soil, oxidizes Sb(III) to Sb(V) under oxic conditions by an unknown mechanism. Genomic analysis of ST2 reveals a gene of unknown function in an arsenic resistance (ars) operon that we term arsO. The transcription level of arsO was significantly upregulated by the addition of Sb(III). ArsO is predicted to be a flavop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…For example, the abundance of arsC (As V reductase) and arsM is significantly and positively correlated with the concentration of total As or As III in the soil solution . As III concentration is also positively correlated with the abundance of aoxA (As III oxidase small subunit), aoxB (As III oxidase large subunit), and arsH (arsenical resistance protein) in mining soils …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the abundance of arsC (As V reductase) and arsM is significantly and positively correlated with the concentration of total As or As III in the soil solution . As III concentration is also positively correlated with the abundance of aoxA (As III oxidase small subunit), aoxB (As III oxidase large subunit), and arsH (arsenical resistance protein) in mining soils …”
Section: Discussionmentioning
confidence: 99%
“…74 As III concentration is also positively correlated with the abundance of aoxA (As III oxidase small subunit), aoxB (As III oxidase large subunit), and arsH (arsenical resistance protein) in mining soils. 75 Environmental Implications. The co-occurrence of As III and MAs III in paddy soils exacerbates the challenge of mitigating As accumulation in the rice grains.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Consistently, both anoA -containing strain AsSb1 and anoA -encoding MAGs isolated or retrieved from XKS tailing in this study belong to the same order as the family Rhizobiaceae . Further, multiple known Sb­(III) oxidizers, such as Allorhizobium , Ensifer , Agrobacterium , and Rhizobium , were also affiliated with these lineages. , On the other hand, other known Sb­(III) oxidizing populations, such as Thiobacillus and Pseudomonas , may utilize different mechanisms for Sb­(III) oxidation. For instance, the arsO gene encoding a homologue of flavoprotein monooxygenase was reported to mediate Sb­(III) oxidation in various microorganisms, including Thiobacillus and Pseudomonas . Furthermore, the extracellular superoxide has been shown to mediate Sb­(III) oxidation in Pseudomonas . , These observations suggested that various functional genes may be responsible for Sb­(III) oxidation.…”
Section: Discussionmentioning
confidence: 99%